Effects of alkaline and acid solutions on glass/epoxy composites - Amaro, A.M.; Reis, P.N.B.; Neto, M.A.; Louro, C. (Polymer degradation and stability, 2013)
Composite structures can be exposed to a range of corrosive environments during their in-service life, which causes degradation in terms of material properties. The effect of alkaline and acid solutions on the GRP mechanical properties can be found in open literature, but the studies presented are not sufficient to establish a full knowledge of this subject. In this paper the flexural properties and the impact strength of a glass fibre/epoxy composite after immersion in hydrochloric acid (HCl) and sodium hydroxide (NaOH) were analysed. Independently of the solution, the flexural strength and the flexural modulus decrease with the exposure time. However, alkaline solution promotes higher decrease of the flexural properties than the acid solution. The same tendency was observed for impact strength.